Peningkatan Perlindungan pada Sistem Operasi Windows terhadap Gangguan Malware (International Forum of Researchers and Lecturers, 2024)
As a popular platform, Windows faces increasingly complex and diverse malware threats. This research evaluates Windows security weaknesses and finds effective methods of mitigating malware attacks. To ensure the validity of the results, the analysis was conducted through literature review, protection method evaluation, and data triangulation. The results show that layered protection methods, which include implementing firewalls, antivirus, and regular system updates, are highly effective in combating different types of malware, such as ransomware, trojans, and spyware. In addition, the use of machine learning and artificial intelligence helps detect threats in real-time. This research provides practical advice for developers and users on how to improve Windows security through a combination of proactive and reactive measures. It also suggests that users be more aware of cybersecurity. The results of this research are expected to serve as a reference for the development of more secure operating systems in the future.